2002
DOI: 10.2320/matertrans.43.585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-Deformation of Austenite on Shape Memory Properties in Fe-Mn-Si-based Alloys Containing Nb and C

Abstract: The shape memory properties of Fe-Mn-Si-based alloys containing Nb and C are further improved by pre-rolling of the solutiontreated austenite and the subsequent ageing treatment. For an Fe-28Mn-6Si-5Cr-0.53Nb-0.06C (mass%) alloy, 90% of an initial 4% strain is recovered on heating without any previous training treatment, if the alloy in austenitic state is rolled by 6-14% at 870 K and aged at 1070 K for 10 min to produce NbC precipitates. In the same condition, the alloy develops shape recovery stresses of 255… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 6 publications
0
38
1
Order By: Relevance
“…In Fe-Mn shape memory alloys it has been found that the shape memory effect is improved if precipitates are introduced [14]. It has been also shown that the presence of precipitates in addition to a small grain size and a selected crystallographic texture lead to good pseudoelastic properties in Fe-Mn-Ni alloys [15].…”
mentioning
confidence: 93%
“…In Fe-Mn shape memory alloys it has been found that the shape memory effect is improved if precipitates are introduced [14]. It has been also shown that the presence of precipitates in addition to a small grain size and a selected crystallographic texture lead to good pseudoelastic properties in Fe-Mn-Ni alloys [15].…”
mentioning
confidence: 93%
“…For the industrial application of coupling pipes in civil engineering, it is, in most cases, required to increase the proof stress of the alloy from the present 250 to 400 MPa and the shape recovery strain of 2.5% at present to over 3.5%. In order to improve the SME and the strength of materials, various investigations have been made such as centrifugal casting, 3) precipitation hardening, [4][5][6] thermomechanical training, 7,8) and high-speed deformation. 9,10) There are two points to improve the SME.…”
Section: Introductionmentioning
confidence: 99%
“…The precipitate shape dependence on the elastic strain energy is thus important in understanding shape changes during the growth and coarsening of precipitates. At the early stage of precipitation, however, small cube shape precipitates with the size of several nanometers in edge width 7,15,33) are formed without misfit dislocations. At this stage of formation of coherent precipitates, because of the minimum interfacial energy of {100} interfacial planes 34) and the minimum elastic strain energy of the cube, 27) the precipitates are formed in a cube shape with {100} interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] The origin of the SME in this alloy is the reversion of the stress-induced "-martensite phase to the parent -austenite that occurs by the movements of the Shockley partial dislocations on heating the material above the A f temperature. 1,2,12) Among the proposed methods of improving the SME of Fe-Mn-Si based shape memory alloys, precipitation hardening seems to be a suitable one to the industrial applications without the necessity of performing repeated thermal cycles and deformation.…”
Section: Introductionmentioning
confidence: 99%